2016
DOI: 10.1021/acsami.5b11023
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene Derivative Emitting Red or near-Infrared Light with Monomer/Excimer Conversion and Its Application to Ratiometric Detection of Hypochlorite

Abstract: Fluorescent sensors are attractive and versatile tools for both chemical sensing and biological imaging. Herein, a novel pyrene derivative fluorophore, Py-Cy, possessing the monomer/excimer conversion feature, was synthesized; and the design rationale for this fluorophore is combination of extending conjugation length and incorporating donor-π-acceptor structure. The positively charged Py-Cy shows quite good water solubility and exhibits absorption in the visible-light range, and its monomer and excimer emit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(65 citation statements)
references
References 48 publications
1
63
0
1
Order By: Relevance
“…S40-S44 in ESI †). [12][13][14] Derivative C2 was synthesized by condensation of 1,2,3,3-tetramethyl-3H-indol-1-ium with 2,7-azaindole-3-carboxaldehyde in ethanol (Scheme 2). 15 The structure of C2 was characterized by various spectroscopic and analytical studies ( Fig.…”
Section: Synthesis Of the Photosensitizers Based On Hemicyanine Derivmentioning
confidence: 99%
“…S40-S44 in ESI †). [12][13][14] Derivative C2 was synthesized by condensation of 1,2,3,3-tetramethyl-3H-indol-1-ium with 2,7-azaindole-3-carboxaldehyde in ethanol (Scheme 2). 15 The structure of C2 was characterized by various spectroscopic and analytical studies ( Fig.…”
Section: Synthesis Of the Photosensitizers Based On Hemicyanine Derivmentioning
confidence: 99%
“…Although hydroboranes and borohydrides have been among the most popular and selective reducing agents since the 1950s, their sensitivity to aerobic oxidation or hydrolysis has constrained their applications as ROSresponsive materials.The reactivity of hydroboranes is tamed by the formation of adducts with aLewis base. [13,14] Selective oxidative hydrolysis of the BÀHb onds of 1·BH 3 by aq. [10] Furthermore,C urran, Lacôte and co-workers have demonstrated that NHC boranes can perform as either radical [11] or ionic [9,12] reductants.…”
mentioning
confidence: 99%
“…Because of its low polarity, 1·BH 3 reversibly forms colloidal aggregates,f acilitating pyrene excimer emission. [13,14] Selective oxidative hydrolysis of the BÀHb onds of 1·BH 3 by aq. HOCl results in the formation of the imidazolium salt 1·H + , which exclusively emits as ad istinct monomeric species.…”
mentioning
confidence: 99%
“…As a noninvasive imaging method with high sensitivity, pure optical detection/imaging techniques have been employed to detect and visualize various cancers and even detect lymph node metastasis . Nevertheless, based on diffuse‐light‐based imaging, pure optical detection techniques have some limitations such as relatively low spatial resolution and penetration depth because of strong light scattering in deep tissue . On the other hand, optoacoustic (OA) imaging, also known as photoacoustic (PA) imaging, integrates the good contrast and high sensitivity attainable in optical imaging with the deep penetration and high resolution of ultrasound .…”
Section: Introductionmentioning
confidence: 99%